2007
DOI: 10.1073/pnas.0702410104
|View full text |Cite
|
Sign up to set email alerts
|

TRF2 is required for repair of nontelomeric DNA double-strand breaks by homologous recombination

Abstract: TRF2 (telomeric repeat binding factor 2) is an essential component of the telomeric cap, where it forms and stabilizes the T-loop junctions. TRF2 forms the T-loops by stimulating strand invasion of the 3 overhang into duplex DNA. TRF2 also has been shown to localize to nontelomeric DNA double-strand breaks , but its functional role in DNA repair has not been examined. Here, we present evidence that TRF2 is involved in homologous recombination (HR) repair of nontelomeric double-strand breaks. Depletion of TRF2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 23 publications
5
100
0
Order By: Relevance
“…To further examine the fidelity of NHEJ in a more quantitative way, we sequenced the junctions of the rescued plasmids and compared the fidelity between the two groups. Although the process of NHEJ is often associated with deletions or insertions, 4,21,22,23 the chance of acquiring insertions in eyelids fibroblasts is extremely slim (0-15%) (Supplementary Table S2), so it is not feasible to analyze the change of insertion sizes with age in these cell lines. We therefore systematically compared the sizes of deletions at the junction areas.…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the fidelity of NHEJ in a more quantitative way, we sequenced the junctions of the rescued plasmids and compared the fidelity between the two groups. Although the process of NHEJ is often associated with deletions or insertions, 4,21,22,23 the chance of acquiring insertions in eyelids fibroblasts is extremely slim (0-15%) (Supplementary Table S2), so it is not feasible to analyze the change of insertion sizes with age in these cell lines. We therefore systematically compared the sizes of deletions at the junction areas.…”
Section: Resultsmentioning
confidence: 99%
“…HCA2 cells. Our previous analysis of integrated clones indicated that transfection with 0.1 μg of plasmid results in the integration of a single copy of the reporter per genome (18). Three separate transfections were performed, giving rise to three independent pools of integrants.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the effect of replicative senescence on DNA DSB repair by HR, we integrated a HR reporter cassette (Fig. 1A) (6,10,18) into the genome of HCA2 cells, a primary foreskin fibroblast strain, at population doubling (PD)26. The challenge of studying HR in the context of replicative senescence is that the reporter construct must be integrated in primary (nonimmortalized cells).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies described first in this laboratory showed that telomeric DNA is highly prone to replication fork slippage, and thus, the binding of TRF2 to slipped structures may be key in stopping further fork slippage and preventing the generation of deleterious structures (19). Moreover, TRF2 prevents NHEJ at non-telomeric sites through its basic domain (22). * This work was supported by National Institutes of Health Grants GM31819 hRap1 was first identified by yeast two hybrid analysis with hTRF2 as a bait (10).…”
mentioning
confidence: 99%